Business Management - Burrow, James L.; Kleindl, Brad. (Mason, OH. : South-Western, Cengage Learning, 2013)
With the focus shifted to business management, BUSINESS MANAGEMENT 13E, formerly Business Principles and Management, approaches business operations from the entrepreneurial and management perspective. Finance, marketing, and human resources are some of the topics explored.
Keywords: Management; Human resource management; Business